HBV Infection Status Indicates Different Risks of Synchronous and Metachronous Liver Metastasis in Colorectal Cancer: A Retrospective Study of 3132 Patients with a 5-Year Follow-Up - Zhou J; Guo X; Huang P; Tan S; Lin R; Zhan H; Wu X; Li T; Huang M; Huang M (Cancer Management and Research, 2022)
Jiaming Zhou1,2 *, Xiaoyan Guo3 *, Pinzhu Huang1,2 *, Shuyun Tan,1,2 Rongwan Lin,4 Huanmiao Zhan,5 Xiaofeng Wu,6 Tuoyang Li,1,2 Mingzhe Huang,1,2 Meijin Huang1,2 1Department of Colon and Rectum Surgery, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 2Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 3Department of Infectious Diseases, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 4Department of Clinical Laboratory, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 5Department of Pathology, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 6Department of Medical Records Management, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China* These authors contributed equally to this workCorrespondence: Meijin Huang, The Sixth Affiliated Hospital of Sun Yat-sen University, No. 26 Yuancun Erheng Road, Tianhe District, Guangzhou, Guangdong, People’s Republic of China, Tel +8613924073322, Fax +8620-38254221, Email hmjin@mail.sysu.edu.cnPurpose: Previous studies on the effect of hepatitis B virus (HBV) infection on colorectal liver metastasis (CRLM) are contradictory. This study revealed different, more specific impacts of HBV on CRLM.Patients and Methods: A total of 3132 colorectal cancer patients treated from 2013 to 2015 were analyzed retrospectively and followed up for five years. The patients were divided into three groups: group A (chronic HBV infection, CHB); group B, (occult HBV infection, OHB) and group C (no HBV infection, NHB). The risk factors for CRLM, 5-year overall survival (OS), and liver disease-free survival (LDFS) were analyzed.Results: A total of 905 patients (28.9%) had CRLM, with poor survival compared to those without CRLM (P < 0.01). The incidence of CRLM was 33.41% (138/413) in group A, 21.63% (138/638) in group B and 30.23% (629/2081) in group C (P < 0.05). Synchronous colorectal cancer liver metastasis (SYN-CRLM) was found in 425 patients (13.57%). CHB increased the risk of SYN-CRLM (P < 0.01), with a worse prognosis (P < 0.05). Metachronous colorectal cancer liver metastasis (MET-CRLM) was found in 480 patients (15.33%). OHB decreased the risk of MET-CRLM after surgery (P = 0.02), with a better 5-year LDFS (P = 0.01). Even without surgery, patients with OHB showed a lower incidence rate of MET-CRLM (P < 0.01).Conclusion: The incidence of CRLM in this study was approximately 28.9%. Surgery and different HBV infection statuses affected the occurrence of CRLM. Chronic HBV infection increased the risk of SYN-CRLM with poor prognosis. Occult HBV infection reduced the risk of MET-CRLM with better LDFS after surgery.Keywords: colorectal cancer, liver metastasis, hepatitis B virus, chronic HBV infection, occult HBV infection